Distinctive features of initial breakdown process between ground and cloud discharges - Mohd Esa, Mona Riza; Ahmad, Mohd Riduan; Cooray, Vernon (2012)
This paper investigates the existence of distinctive features of initial breakdown process between ground (CG) and cloud (IC) discharges. 10 ground discharge and 10 cloud discharge waveforms have been selected from a collection of waveforms measured using fast broadband antenna system. The measurements were carried out in Uppsala, Sweden from June to August 2010. Major distinctive features are discovered between the initial breakdown process of ground and cloud discharges. Within the first 1 ms duration, the initial breakdown process of CG has more than twice number of pulses, more bipolar pulses than unipolar pulses, and shorter inter-pulse duration when compared to IC.